PRINSIP-PRINSIP DASAR DALAM Al-QUR’AN TENTANG PENGELOLAAN LINGKUNGAN HIDUP - Ginda Harahap (An-Nida', 2018)
Good environmental management, is the only opportunity and choice for humans to be able to exist and live on this earth. Massive environmental damage in various parts of the world has brought about many  disasters.     And it is no exception in Indonesia that disasters that come and go, such as earthquakes, floods, landslides, tsunamis, volcanic eruptions and others, can be concluded due to damage to environmental balance.  In Islamic perspective (Al-Qur'an), Allah has long explained to humans some principles that must be implemented in interacting with the environment, so that humans are protected from di sasters and disasters.   In this case, humans must not only understand the balance and regularity of the ecosystem (environment), as Allah has created, but also must preserve  ecosystems (environment), in accordance with the law of balance, and this is part of the task of human as khalifah   on earth.